Genome-Wide Sequence Variation among Mycobacterium avium Subspecies paratuberculosis Isolates: A Better Understanding of Johne’s Disease Transmission Dynamics - Hsu, Chung-Yi; Wu, Chia-wei; Talaat, Adel M. (Frontiers in Microbiology, 2011)
Mycobacterium avium subspecies paratuberculosis (M. ap), the causative agent of Johne’s disease (JD), infects many farmed ruminants, wildlife animals and humans. To better understand the molecular pathogenesis of these infections, we analyzed the whole genome sequences of several M. ap and M. avium subspecies avium (M. avium) strains isolated from various hosts and environments. Using Next-generation sequencing technology, all 6 M. ap isolates showed a high percentage of homology (98%) to the reference genome sequence of M. ap K-10 isolated from cattle. However, 2 M. avium isolates (DT 78 and Env 77) showed significant sequence diversity from the reference strain M. avium 104. The genomes of M. avium isolates DT 78 and Env 77 exhibited only 87% and 40% homology, respectively, to the M. avium 104 reference genome. Within the M. ap isolates, genomic rearrangements (insertions/deletions, Indels) were not detected, and only unique single nucleotide polymorphisms (SNPs) were observed among the 6 M. ap strains. While most of the SNPs (~100) in M. ap genomes were non-synonymous, a total of ~ 6000 SNPs were detected among M. avium genomes, most of them were synonymous suggesting a differential selective pressure between M. ap and M. avium isolates. In addition, SNPs-based phylo-genomic analysis showed that isolates from goat and Oryx are closely related to the cattle (K-10) strain while the human isolate (M. ap 4B) is closely related to the environmental strains, indicating environmental source to human infections. Overall, SNPs were the most common variations among M. ap isolates while SNPs in addition to Indels were prevalent among M. avium isolates. Genomic variations will be useful in designing host-specific markers for the analysis of mycobacterial evolution and for developing novel diagnostics directed against Johne’s disease in animals.